Predisclosure Information and Institutional Ownership: A Cross-Sectional Examination of Market Revaluations During Earnings Announcement Periods. - El-Gazzar, Samir M. (The Accounting Review, 1998)
Institutional investors have strong incentives to search for private predisciosure information about companies in their portfolios because of their fiduciary responsibilities and large resource bases. In addition, large institutional ownership may induce a high level of voluntary disclosure prior to earnings announcements. Greater private information acquisition and greater levels of voluntary disclosures prior to earnings releases suggest that the content of the earnings releases by firms with higher institutional ownership is partially preempted in predisciosure market prices. This paper tests the hypothesis that the market price response to the earnings announcements is smaller for securities with higher institutional holdings. The empirical tests provide evidence that the higher the institutional holdings, the lower the market reaction to earnings releases after controlling for security capitalization and the number of analysts following the firm.